High-adhesion wear-resistant polyurethane coating for PC glass plate and preparation method of high-adhesion wear-resistant polyurethane coating
By combining modified polyurethane emulsion and wear-resistant functional agent, a high-adhesion and wear-resistant polyurethane coating was prepared, which solved the problem of insufficient bonding strength and wear resistance of water-based polyurethane coating on PC glass plates, and achieved high adhesion and improved wear resistance of the coating on PC glass plates.
Patent Information
- Application Number
- CN202511056425.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-30
- Publication Date
- 2025-10-17
- Estimated Expiration
- 2045-07-30
AI Technical Summary
Existing waterborne polyurethane coatings have poor bonding strength, wear resistance and scratch resistance on PC glass panels, which limits their application scope. In addition, the high cost makes them unsuitable for large-scale industrial production.
A combination of modified polyurethane emulsion, wear-resistant functional agent and high adhesive is used to prepare a high adhesive containing unsaturated long-chain alkanes and carboxylic acids, combined with nano zinc oxide with a continuous rigid benzene ring structure, to improve the adhesion and wear resistance of the coating.
It achieves high bonding strength, wear resistance and impact resistance. The coating has excellent adhesion performance on PC glass panels and has good resistance to UV aging.
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the field of coating technology, in particular to a high-adhesion wear-resistant polyurethane coating for PC glass plates and a preparation method thereof. BACKGROUND
[0002] As a widely used synthetic material, polyurethane coatings are traditionally solvent-based. These coatings usually contain solvents such as toluene, which are flammable, explosive, highly volatile, and have a strong odor. During use, they can cause air pollution and pose a potential threat to human health. With the increasing awareness of environmental protection, the environmental standards for materials are becoming increasingly stringent. Water-based coatings, which use water as a dispersion medium, have become environmentally friendly materials and are favored by the market. Their low odor and non-polluting properties make water-based coatings increasingly diverse, with production continuing to grow and gradually replacing traditional solvent-based coatings, which are widely used in the market.
[0003] Water-based polyurethane requires high hydrolytic stability of raw materials as water is used as the dispersion medium. Although polyether-based polyurethane can meet the requirements of hydrolysis resistance, its adhesion strength, wear resistance, and scratch resistance are poor, limiting the application range of the product. Although the use of polytetrahydrofuran and polyhexamethylene carbonate diol can produce water-based polyurethane coatings with high adhesion strength, excellent wear resistance, and scratch resistance, the cost is high, which is not conducive to large-scale industrial production, thereby limiting its use and promotion.
[0004] To solve the above problems, the present application provides a high-adhesion wear-resistant polyurethane coating for PC glass plates. SUMMARY
[0005] The present application aims to provide a high-adhesion wear-resistant polyurethane coating for PC glass plates and a preparation method thereof.
[0006] The object of the present application can be achieved by the following technical solutions:
[0007] A high-adhesion wear-resistant polyurethane coating for PC glass plates, comprising the following raw materials: modified polyurethane emulsion 40-60 parts, wear-resistant functional agent 3-5 parts, deionized water 30-50 parts, defoaming agent 1-3 parts, leveling agent 0.2-0.5 parts, dispersing agent 1-1.5 parts;
[0008] The modified polyurethane emulsion comprises the following raw materials by weight: polyethylene glycol 30-50 parts, polyisocyanate 15-25 parts, catalyst 0.03-0.05 parts, dihydroxymethyl acrylate 5-8 parts, organic amine 2-5 parts, solvent 2-5 parts, deionized water 80-100 parts, high-adhesion agent 3-5 parts, and 0.03-0.05 parts of initiator azobisisobutyronitrile;
[0009] The preparation method of the modified polyurethane emulsion comprises the following steps:
[0010] Step A1: vacuum drying polyethylene glycol at 80-100℃ for 1-2h, then adding catalyst and polyisocyanate into the dried polyethylene glycol under inert gas protection, heating to 80-100℃, constant temperature reaction for 2-5h, cooling to 30-40℃, adding dihydroxymethyl acrylate, solvent, heating to 80-100℃ for 3-5h to prepare a prepolymer;
[0011] Step A2: adding deionized water, organic amine into the prepolymer, stirring for 3-4h, then heating to 60-80℃, adding high adhesive, initiator, and reacting for 2-5h to prepare the modified polyurethane emulsion.
[0012] Further, the dispersant is one of polyvinyl pyrrolidone and sodium polyacrylate; the leveling agent is one of water-based acrylate copolymer and polydimethylsiloxane; the defoaming agent is one of tributyl phosphate and fatty alcohol polyoxyethylene ether.
[0013] Further, in step A1, the catalyst is dibutyltin dilaurate; the polyisocyanate is any one of toluene diisocyanate, 1,6-hexylene diisocyanate and isophorone diisocyanate; in step A2, the organic amine is one of n-propylamine and triethanolamine; the solvent is N,N-methyl pyrrolidone.
[0014] Further, in step A2, the preparation method of the high adhesive comprises the following steps:
[0015] Step S1: dissolving cardanol in anhydrous toluene and heating to 60-80℃, adding toluene diisocyanate and catalyst, and reacting for 8-10h, then filtering, washing and vacuum drying at 130-135℃ for 1h to prepare intermediate a, and the reaction synthesis route is as follows:
[0016] , wherein R=C 15 H 31-2n , n=1-3;
[0017] Step S2: dispersing 4,4'-diaminobiphenyl-2,2'-dicarboxylic acid and intermediate a in toluene, stirring at 80-85℃ for 1-3h, then filtering, washing and vacuum drying at 80-100℃ for 3h to prepare the high adhesive, and the reaction synthesis route is as follows: ;
[0018] In the technical scheme, the phenolic hydroxyl group in cardanol is reacted with toluene diisocyanate to obtain an intermediate a containing isocyanate and an unsaturated long chain, and then the amino group of 4, 4 '-diaminobiphenyl-2, 2 '-dicarboxylic acid is reacted with the isocyanate of the intermediate a to obtain a high adhesive containing carboxylic acid structure, unsaturated double bond and long chain alkane.
[0019] Further, in step S1, the catalyst is one of dibutyltin dilaurate and stannous octoate.
[0020] Further, the preparation method of the wear-resistant functional agent comprises the following steps:
[0021] Step B1: polyphenylene sulfide fibers are added into N, N-dimethylformamide, and are stirred and dissolved under nitrogen protection, and are reacted at 100-120 DEG C for 8-10 h, are cooled to 20-30 DEG C, and chloromethyl ether is slowly added dropwise, a catalyst is added dropwise, and is maintained at 50-55 DEG C for 1-2 h, and is filtered, washed and dried to obtain a polyphenylene sulfide intermediate;
[0022] Step B2: nano zinc oxide is vacuum dried at 100-120 DEG C for 6-8 h, and then the dried nano zinc oxide, 3-aminobenzoic acid, 4-diaminopyridine and 1-(3-dimethylaminopropyl)-3-ethyl carbodiimide hydrochloride are added into dichloromethane, and are reacted at 50 DEG C for 3-5 h under an oxygen-free environment, and are cooled, filtered, washed and dried to obtain a nano zinc oxide intermediate, and the reaction synthesis route is as follows:
[0023] ;
[0024] Step B3: the polyphenylene sulfide intermediate and the nano zinc oxide intermediate are added into toluene solution, and are reacted at 60-80 DEG C under nitrogen environment for 8-10 h, and are filtered, washed and dried to obtain the wear-resistant functional agent.
[0025] In the technical scheme, the polyphenylene sulfide is reacted with chloromethyl ether under the catalysis of a catalyst to occur chloromethylation, and a polyphenylene sulfide intermediate is obtained, the nano zinc oxide is esterified with 3-aminobenzoic acid to obtain a functionalized nano zinc oxide intermediate, and the nano zinc oxide is grafted on the polyphenylene sulfide by amination with the chloromethylated polyphenylene sulfide as a matrix to obtain the nano zinc oxide with continuous rigid benzene ring.
[0026] Further, in step B1, the molecular weight of the polyphenylene sulfide is 5000-7000.
[0027] Further, in step B1, the catalyst is anhydrous tin tetrachloride.
[0028] Further, in step B1, the amount ratio of the polyphenylene sulfide to chloromethyl ether is 1 g: (20-25) ml.
[0029] A preparation method of a high-adhesion wear-resistant polyurethane coating for PC glass plates, comprising the following steps:
[0030] Step one: add modified polyurethane emulsion, wear-resistant functional agent, deionized water and leveling agent into a mixer, stir and mix for 1-3 hours to form a premix;
[0031] Step two: stir and mix the defoaming agent, dispersing agent and premix uniformly to form a uniform coating, which can be stored at room temperature.
[0032] The beneficial effects of the present application are:
[0033] (1) The present application uses a high-adhesion agent containing unsaturated long-chain alkanes and carboxylic acid to give the coating high-adhesion and impact resistance. The carboxylic acid group can improve the adhesion of the coating to the PC plate, and the unsaturated long-chain alkanes can undergo free radical polymerization with the coating during the preparation of the coating, thereby uniformly dispersing the high-adhesion agent in the coating. Because the high-adhesion agent can intertwine with each other, it can improve the density and impact resistance of the coating.
[0034] (2) The present application uses nano-zinc oxide containing a continuous rigid benzene ring structure to participate in the preparation of the coating. The continuous benzene ring structure of polyphenyl sulfide can improve the wear resistance of the coating, and nano-zinc oxide as an inorganic nano-metal oxide material can also synergistically improve the wear resistance of the coating. Moreover, the modified nano-zinc oxide has a surface rich in amino groups that can crosslink with the chloromethyl groups in the long chain of chloromethylated polyphenyl sulfide, thereby improving the impact resistance of the coating. DETAILED DESCRIPTION
[0035] The technical solutions of the present application will be described below in conjunction with the embodiments of the present application. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor fall within the scope of protection of the present application.
[0036] Preparation Example 1
[0037] A high-adhesion wear-resistant polyurethane coating for PC glass plates, by weight, comprises the following raw materials: modified polyurethane emulsion 40 parts, wear-resistant functional agent 3 parts, deionized water 30 parts, defoaming agent tributyl phosphate 1 part, leveling agent polydimethylsiloxane 0.2 parts, and dispersing agent polyacrylic acid sodium salt 1 part.
[0038] The preparation method of the coating comprises the following steps:
[0039] Step one: take the weight parts of deionized water, modified polyurethane emulsion, leveling agent polydimethylsiloxane, dispersant polyacrylic acid sodium salt, wear-resistant functional agent, stirring at a speed of 600 rpm for 20 min, forming a mixed emulsion;
[0040] Step two: take the weight parts of defoaming agent tributyl phosphate, wear-resistant functional agent and mixed emulsion, stirring at a speed of 1000 rpm for 15 min, to prepare polyurethane coating.
[0041] The modified polyurethane emulsion includes the following weight parts of raw materials: polyethylene glycol 30 parts, polyisocyanate isophorone diisocyanate 15 parts, catalyst dibutyltin dilaurate 0.03 parts, dihydroxymethyl acrylate 5 parts, organic amine triethylamine 3 parts, solvent N,N-methyl pyrrolidone 2 parts, deionized water 80 parts, high adhesive 4 parts, 0.8 parts of initiator azobisisobutyronitrile;
[0042] The preparation method of the modified polyurethane emulsion includes the following steps:
[0043] Step A1: vacuum dry polyethylene glycol 45 parts at 80℃ for 1h, then under inert gas protection, add 0.03 parts of catalyst dibutyltin dilaurate and 30 parts of polyisocyanate isophorone diisocyanate to the dried polyethylene glycol, heat to 80℃, constant temperature reaction for 2h, cool to 40℃, add 5 parts of dihydroxymethyl acrylate, 2 parts of solvent N,N-methyl pyrrolidone, heat to 80℃ and react for 3h to prepare the prepolymer;
[0044] Step A2: add 80 parts of deionized water, 3 parts of organic amine triethylamine to the prepolymer, stir for 3h, then heat to 60℃, add 5 parts of high adhesive, 0.5 parts of initiator azobisisobutyronitrile, react for 2h to prepare the modified polyurethane emulsion.
[0045] The preparation method of the high adhesive includes the following steps:
[0046] Step S1: dissolve 15g of cardanol in 100ml of anhydrous toluene, heat to 90℃, add 8g of toluene diisocyanate, 0.03g of catalyst dibutyltin dilaurate, react under nitrogen protection for 9h, then filter, wash, and vacuum dry at 130℃ for 1h to prepare the intermediate a;
[0047] Step S2: disperse 13g of 4,4'-diaminobiphenyl-2,2'-dicarboxylic acid and 10g of intermediate a in 50ml of toluene, stir at 80℃ for 3h, then filter, wash, and vacuum dry at 80℃ for 3h to prepare the high adhesive.
[0048] The preparation method of the wear-resistant functional agent includes the following steps:
[0049] Step B1: 1.5 g of polyphenylene sulfide fiber was added to 50 mL of N, N-dimethylformamide, and stirred and dispersed under nitrogen protection. 45 mL of chloromethyl ether was slowly added dropwise at 55°C, and 1.5 mL of catalyst anhydrous tin tetrachloride was added dropwise. The reaction was carried out for 8 h, and the product was obtained by filtering, washing, and precipitating.
[0050] Step B2: 1.3 g of nano-zinc oxide was dried at 120°C under vacuum for 6 h, and then the dried nano-zinc oxide, 1.0 g of 3-aminobenzoic acid, 0.02 g of 4-diamino pyridine, and 0.15 g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride were heated to 50°C and reacted for 3 h under an oxygen-free environment. The product was obtained by cooling, filtering, washing, and drying.
[0051] Step B3: 1.5 g of the polyphenylene sulfide intermediate and 1.2 g of the nano-zinc oxide intermediate were added to 50 mL of toluene solution, and the reaction was carried out for 8 h under nitrogen at 80°C. The product was obtained by filtering, washing, and drying.
[0052] Example 1
[0053] A high-adhesion wear-resistant polyurethane coating for PC glass plates, by weight, includes the following raw materials: 40 parts of modified polyurethane emulsion, 3 parts of wear-resistant functional agent, 30 parts of deionized water, 1 part of antifoaming agent tributyl phosphate, 0.2 parts of leveling agent polydimethylsiloxane, and 1 part of dispersant polyacrylic acid sodium salt.
[0054] The preparation method of the coating includes the following steps:
[0055] Step one: take the weight parts of deionized water, modified polyurethane emulsion, leveling agent polydimethylsiloxane, dispersant polyacrylic acid sodium salt, and wear-resistant functional agent, and stir at a speed of 600 rpm for 20 min to form a mixed emulsion;
[0056] Step two: take the weight parts of antifoaming agent tributyl phosphate and wear-resistant functional agent, and stir with the mixed emulsion at a speed of 1000 rpm for 15 min to obtain a polyurethane coating.
[0057] The modified polyurethane emulsion and the wear-resistant functional agent are the same as in Preparation Example 1.
[0058] Example 2
[0059] A high-adhesion wear-resistant polyurethane coating for PC glass plates, by weight, includes the following raw materials: 55 parts of modified polyurethane emulsion, 4.5 parts of wear-resistant functional agent, 35 parts of deionized water, 2 parts of antifoaming agent tributyl phosphate, 0.4 parts of leveling agent polydimethylsiloxane, and 1.3 parts of dispersant polyacrylic acid sodium salt.
[0060] The preparation method of the coating includes the following steps:
[0061] Step one: take the weight parts of deionized water, modified polyurethane emulsion, leveling agent polydimethylsiloxane, dispersant polyacrylic acid sodium salt, wear-resistant functional agent at the speed of 600 rpm stirring 20 min, forming a mixed emulsion;
[0062] Step two: take the weight parts of defoamer tributyl phosphate, wear-resistant functional agent and mixed emulsion at the speed of 1000 rpm stirring 15 min, prepared polyurethane coating.
[0063] Among them, the modified polyurethane emulsion and wear-resistant functional agent are the same as in preparation example 1.
[0064] Example 3
[0065] A kind of high bonding wear-resistant polyurethane coating for PC glass plate, by weight parts, includes the following raw materials: modified polyurethane emulsion 60 parts, wear-resistant functional agent 5 parts, deionized water 50 parts, defoamer tributyl phosphate 3 parts, leveling agent polydimethylsiloxane 0.5 parts, dispersant polyacrylic acid sodium salt 1.5 parts.
[0066] The preparation method of the coating includes the following steps:
[0067] Step one: take the weight parts of deionized water, modified polyurethane emulsion, leveling agent polydimethylsiloxane, dispersant polyacrylic acid sodium salt, wear-resistant functional agent at the speed of 600 rpm stirring 20 min, forming a mixed emulsion;
[0068] Step two: take the weight parts of defoamer tributyl phosphate, wear-resistant functional agent and mixed emulsion at the speed of 1000 rpm stirring 15 min, prepared polyurethane coating.
[0069] Among them, the modified polyurethane emulsion and wear-resistant functional agent are the same as in preparation example 1.
[0070] Comparative example 1
[0071] A kind of high bonding wear-resistant polyurethane coating for PC glass plate, by weight parts, includes the following raw materials: modified polyurethane emulsion 55 parts, wear-resistant functional agent 4.5 parts, deionized water 35 parts, defoamer tributyl phosphate 2 parts, leveling agent polydimethylsiloxane 0.4 parts, dispersant polyacrylic acid sodium salt 1.3 parts.
[0072] The preparation method of the coating includes the following steps:
[0073] Step one: take the weight parts of deionized water, modified polyurethane emulsion, leveling agent polydimethylsiloxane, dispersant polyacrylic acid sodium salt, wear-resistant functional agent at the speed of 600 rpm stirring 20 min, forming a mixed emulsion;
[0074] Step two: take the weight parts of the anti-foaming agent tributyl phosphate, wear-resistant functional agent and mixed emulsion at 1000 rpm speed stirring 15 min, polyurethane coating is prepared.
[0075] Among them, the difference between the modified polyurethane emulsion preparation example 1 is not to join the high adhesive.
[0076] Comparative example 2
[0077] A kind of high adhesive wear-resistant polyurethane coating for PC glass plate, by weight parts, includes the following raw materials: modified polyurethane emulsion 55 parts, deionized water 35 parts, anti-foaming agent tributyl phosphate 2 parts, leveling agent polydimethylsiloxane 0.4 parts, dispersing agent polyacrylic acid sodium salt 1.3 parts.
[0078] The preparation method of the coating includes the following steps:
[0079] Step one: take the weight parts of the deionized water, modified polyurethane emulsion, leveling agent polydimethylsiloxane, dispersing agent polyacrylic acid sodium salt at the speed of 600 rpm stirring 20 min, form mixed emulsion;
[0080] Step two: take the weight parts of the anti-foaming agent tributyl phosphate, wear-resistant functional agent and mixed emulsion at 1000 rpm speed stirring 15 min, polyurethane coating is prepared.
[0081] Among them, the difference between the preparation example 1 is that the wear-resistant functional agent is not added.
[0082] Comparative example 3
[0083] A kind of high adhesive wear-resistant polyurethane coating for PC glass plate, by weight parts, includes the following raw materials: modified polyurethane emulsion 55 parts, deionized water 35 parts, anti-foaming agent tributyl phosphate 2 parts, leveling agent polydimethylsiloxane 0.4 parts, dispersing agent polyacrylic acid sodium salt 1.3 parts.
[0084] The preparation method of the coating includes the following steps:
[0085] Step one: take the weight parts of the deionized water, modified polyurethane emulsion, leveling agent polydimethylsiloxane, dispersing agent polyacrylic acid sodium salt at the speed of 600 rpm stirring 20 min, form mixed emulsion;
[0086] Step two: take the weight parts of the anti-foaming agent tributyl phosphate, wear-resistant functional agent and mixed emulsion at 1000 rpm speed stirring 15 min, polyurethane coating is prepared.
[0087] Among them, the difference between the preparation example 1 is that the wear-resistant functional agent is not added.
[0088] Performance test
[0089] The paint is coated on the surface of clean PC glass plate, and is coated flat by rolling, and is placed for 5 min, and is cured into a film under a light curing machine, and performance test is carried out, and the test results are shown in the following table; the ultraviolet light accelerated aging experiment is carried out for 2 months according to the standard GB / T23987-2009, whether the coating appears powdering or yellowing phenomenon is observed, the ultraviolet light source is a lamp tube with UVA-340nm specification, and the irradiation intensity is 0.60W / m 2 ; the coating adhesion strength is determined according to GB / T16777-2008; the coating film is installed on the testing machine, the middle line of the coating film surface in the vertical direction is kept on a line with the center of the testing machine clamp, and the coating film is stretched to failure, and the maximum tensile force of the coating film is recorded as the adhesion strength of the coating film; the coating wear resistance test is carried out according to GB / T1768-2006, and a rubber wheel is used in the wear resistance test, and the rotating speed is (60±2) r / min; the coating impact resistance is tested according to GB / T1732-1993.
[0090] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Bond strength / Mpa 3.6 3.8 3.5 1.2 3.3 1.0 Wear resistance (g) 0.023 0.021 0.024 0.026 0.046 0.075 UV aging resistance (600h) No yellowing or powdering No yellowing or powdering No yellowing or powdering No yellowing or powdering Extensive yellowing and severe chalking Extensive yellowing and severe chalking Impact resistance / cm 42 45 43 40 36 33
[0091] It can be seen from the above table that in the ultraviolet aging resistance test, the adhesion strength test, the wear resistance test and the impact resistance test, the high adhesive added in the embodiments 1-3 contains a large amount of long-chain unsaturated alkane, which can be closely connected with the coating during the preparation of the coating, and the carboxyl group and the urethane group contained therein can improve the adhesion strength of the coating, the amino-rich wear-resistant functional agent can crosslink with the chloromethyl in the long chain of the chloromethylated polyphenyl sulfide, so that the coating has high impact resistance and excellent wear resistance and good ultraviolet aging resistance. The coating prepared in Comparative Example 1 does not contain a high adhesive, and because of the lack of a rigid benzene ring and a carboxyl group and an unsaturated long chain, the adhesion performance is poor, the wear resistance and the impact resistance are relatively poor compared with the embodiments 1-3. The coating prepared in Comparative Example 2 does not contain a wear-resistant functional agent, so the wear resistance is poor, and because it does not have nano zinc oxide and crosslinked amino and chloromethyl, the effect in the ultraviolet aging resistance test and the impact resistance test is also poor. In Comparative Example 3, no high adhesive and wear-resistant functional agent are added in the preparation of the coating, so the performance in the test is the worst.
[0092] The above content is only an example and description of the concept of the present application, and those skilled in the art can make various modifications or supplements or use similar ways to replace the described specific embodiments, as long as they do not deviate from the concept of the present application or exceed the scope defined by the present claims, which shall belong to the protection scope of the present application.
Claims
1. A high-bonding, wear-resistant polyurethane coating for PC glass plates, characterized in that: The raw materials include the following by weight: 40-60 parts of modified polyurethane emulsion, 3-5 parts of wear-resistant functional agent, 30-50 parts of deionized water, 1-3 parts of defoaming agent, 0.2-0.5 parts of leveling agent, and 1-1.5 parts of dispersant; The modified polyurethane emulsion comprises the following raw materials in parts by weight: 30-50 parts of polyethylene glycol, 15-25 parts of polyisocyanate, 0.03-0.05 parts of catalyst, 5-8 parts of dihydroxymethyl acrylate, 2-5 parts of organic amine, 2-5 parts of solvent, 80-100 parts of deionized water, 3-5 parts of high binder, and 0.03-0.05 parts of initiator; The preparation method of the modified polyurethane emulsion comprises the following steps: Step A1: vacuum drying polyethylene glycol at 80-100°C for 1-2 hours, then adding a catalyst and a polyisocyanate to the dried polyethylene glycol under inert gas protection, raising the temperature to 80-100°C, reacting at this temperature for 2-5 hours, cooling to 30-40°C, adding dihydroxymethyl methacrylic acid and a solvent, raising the temperature to 80-100°C, and reacting for 3-5 hours to obtain a prepolymer; Step A2: Deionized water and organic amine are added to the prepolymer, and the mixture is stirred for 3-4 hours. The mixture is then heated to 60-80° C., a high binder and azobisisobutyronitrile initiator are added, and the mixture is reacted for 2-5 hours to obtain a modified polyurethane emulsion.
2. The high-bonding and wear-resistant polyurethane coating for PC glass plates according to claim 1, characterized in that: The dispersant is one of polyvinyl pyrrolidone and sodium polyacrylate; the leveling agent is one of water-based acrylic acid ester copolymer and polydimethylsiloxane; and the defoaming agent is one of tributyl phosphate and fatty alcohol polyoxyethylene ether.
3. The high-bonding and wear-resistant polyurethane coating for PC glass plates according to claim 1, characterized in that: In step A1, the catalyst is dibutyltin dilaurate; the polyisocyanate is any one of toluene diisocyanate, 1,6-hexamethylene diisocyanate, and isophorone diisocyanate; in step A2, the organic amine is one of n-propylamine and triethanolamine; and the solvent is N,N-methylpyrrolidone.
4. The high-bonding and wear-resistant polyurethane coating for PC glass plates according to claim 1, characterized in that: In step A2, the preparation method of the high binder comprises the following steps: Step S1: dissolving cardanol in anhydrous toluene and heating to 60-80°C, adding toluene diisocyanate and a catalyst, reacting for 8-10 hours, filtering, washing, and vacuum drying at 130-135°C for 1 hour to obtain intermediate a; Step S2: Disperse 4,4'-diaminobiphenyl-2,2'-dicarboxylic acid and intermediate a in toluene, stir at 80-85°C for 1-3 hours, filter, wash, and vacuum dry at 80-100°C for 3 hours after the reaction to obtain a high binder.
5. The high-bonding and wear-resistant polyurethane coating for PC glass plates according to claim 4, characterized in that: In step S1, the catalyst is one of dibutyltin dilaurate and stannous octoate.
6. The high-bonding and wear-resistant polyurethane coating for PC glass plates according to claim 1, characterized in that: The preparation method of the wear-resistant functional agent comprises the following steps: Step B1: adding polyphenylene sulfide fiber to N,N-dimethylformamide, stirring and dissolving under nitrogen protection, reacting at 100-120°C for 8-10 hours, cooling to 20-30°C, slowly adding chloromethyl ether dropwise, adding a catalyst dropwise, maintaining the reaction at 50-55°C for 1-2 hours, filtering, washing, and drying to obtain a polyphenylene sulfide intermediate; Step B2: Dry the nano-zinc oxide at 100-120° C. in a vacuum oven for 6-8 hours, then add the dried nano-zinc oxide, 3-aminobenzoic acid, 4-diaminopyridine, and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to dichloromethane, raise the temperature to 50° C., react in an oxygen-free environment for 3-5 hours, cool, filter, wash, and dry to obtain a nano-zinc oxide intermediate. Step B3: Add the polyphenylene sulfide intermediate and the nano zinc oxide intermediate to a toluene solution, react at 60-80° C. in a nitrogen environment for 8-10 hours, filter, wash, and dry to obtain a wear-resistant functional agent.
7. The high-bonding and wear-resistant polyurethane coating for PC glass plates according to claim 6, characterized in that: In step B1, the molecular weight of the polyphenylene sulfide is 5000-7000.
8. The high-bonding and wear-resistant polyurethane coating for PC glass plates according to claim 6, characterized in that: In step B1, the catalyst is anhydrous tin tetrachloride.
9. The high-bonding and wear-resistant polyurethane coating for PC glass plates according to claim 6, characterized in that: In step B1, the ratio of polyphenylene sulfide to chloromethyl ether is 1 g: (20-25) ml.
10. The method for preparing a high-bonding and wear-resistant polyurethane coating for PC glass plates according to claim 1, wherein: The following steps are involved: Step 1: Add modified polyurethane emulsion, wear-resistant functional agent, deionized water and leveling agent into a mixer and stir for 1-3 hours to form a premix; Step 2: Stir and mix the defoamer, dispersant and premix evenly to form a uniform coating, and store the discharged material at room temperature.
Citation Information
Patent Citations
Modified polyphenylene sulfide coating and application thereof
CN102676048A
Heatproof ultraviolet-resistant polyurethane paint
CN107353806A
Preparation method of high-dispersion zinc oxide
CN114479184A
Wear-resistant waterborne polyurethane coating and preparation method thereof
CN117659843A
UV curing printing ink and preparation method thereof
CN120137449A